Stereotyping as inductive hypothesis testing - Fiedler, Klaus, 1951- (European monographs in social psychology., 2004)
Stereotyping as Inductive Hypothesis Testing explicates the proposition that many stereotypes originate not so much in individual brains, but in the stimulus environment that interacts with and constitutes the social individual.